Prevalence of PTSD and its associated risk factors among trauma patients attended Orthopaedic Clinics and wards in HUSM AND HRPZII - Jaapar, Sharifah Zubaidiah Syed (2010)
PTSD is prevalent among the trauma patients in Orthopaedic Wards and Clinic. An easy, cheap and reliable tool screening tool is needed to screen the possible PTSD symptoms in order to provide early intervention and to prevent further complication. This study was aimed to validate the Malay version ofTSQ in order to determine the prevalence of PTSD and its associated risk factors among trauma patients who attended Orthopaedic Wards and Clinic in HUSM and HRPZII. It was a cross sectional study and divided into two stages. The first stage was the validation of the Malay version TSQ and the second stage was a prevalence study. There were 201 participants in the study from Orthopaedic Wards and Clinic in HUSM and HRPZII. Data were collected by using the validated Malay version TSQ, sociodemographic data form and interviewed with CAPS. CAPS was used as a gold standard to diagnose PTSD as well as to compare with the Malay version ofTSQ. Malay version ofTSQ has good internal consistency (a= 0.733) and good concurrent validity with CAPS. At cut-off score 5 or more, the sensitivity and specificity were 0.8 and 0.85 respectively. The negative predictive value was 0.96 but the positive predictive value was low (0.48). The prevalence of PTSD among trauma patients who attended Orthopaedic Wards and Clinic in HUSM and HRPZII was 24.9%. Fear during trauma had shown to be a significant risk factor of developing PTSD (OR=2.41, (95% CI 1.11, 5.20). Praying was a significantly common means used by respondents to cope with trauma. There was also significant association between support received from professionals and PTSD symptoms Malay version ofTSQ sa valid, cheap and reliable tool for screening PTSD. 24.9% of trauma patients in Orthopaedic Wards and Clinics in HUSM and HRPZII had PTSD.